At the Intersection of Major and Minor Spliceosomes: Crosstalk Mechanisms and Their Impact on Gene Expression - Akinyi, Maureen V.; Frilander, Mikko J. (Frontiers in Genetics, 2021)
Many eukaryotic species contain two separate molecular machineries to remove non-coding intron sequences from pre-mRNA molecules. The majority of introns (more than 99.5% in humans) are recognized and excised by the major spliceosome, which utilizes relatively poorly conserved sequence elements at the 5’ and 3’ ends of the intron that are used for intron recognition and in subsequent catalysis. In contrast, the minor spliceosome targets a rare group of introns (approximately 0.5% in humans) with highly conserved sequences at the 5’ and 3’ ends of the intron. Minor introns coexist in the same genes with major introns and while the two intron types are spliced by separate spliceosomes, the two splicing machineries can interact with one another to shape mRNA processing events in genes containing minor introns. Here, we review known cooperative and competitive interactions between the two spliceosomes and discuss the mechanistic basis of the spliceosome crosstalk, its regulatory significance, and impact on spliceosome diseases.